(untitled) (Teología, 2015)
Gesché proposes in this text of maturity, a praise of theology, to paraphrase Erasmus. It does suggest one way: praise from oblivion (as a possibility to rediscover the words of faith); praise of theology (placing in their proper place in the concert of other sciences); praise the future (which is built with courage and without fear); and a praise of life (lived as theological adventure).